Study on Public and Private Expenditure on Research and Development: An Integrative Report - Caesar B. Cororaton (Philippine Institute for Development Studies (PIDS), 1999)
This paper puts together the key results and insights of various papers written under the project "Study on Public and Private Expenditure on Research and Development (R&D)". It devotes a section that deals with the problem in the present context. In addition, it provides statistical information and accounting system that gives direction on its improvements to generate quick and accurate set of information related to R&D and science and technology (S&T). Patterns of developments in these areas are also included with a focus on the trends of R&D expenditure, R&D manpower and the economic development levels. Comparison of rate of return to R&D in investment here and abroad is made. Using the detailed descriptions of the development of the S&T in South Korea, Taiwan, and New Zealand, the policy case in the Philippines is set up.
Keywords: 330; science and technology; rate of return; research and development sector; total factor productivity